"Старообрядницький Єрусалим". З історії поселення липованів у с. Біла Криниця на Буковині - Таранець, С. (Краєзнавство, 2019)
У статті досліджено основні віхи історії Білої Криниці як одного з провідних всесвітніх центрів
старообрядців та заснування в селі Білокриницької церковної ієрархії. Розкрито політику австрійського
та російського урядів стосовно місцевих старовірів. This article describes the main milestones in history of Bila Krynytsia as one of the leading world centers
of Old Believers and foundation of Bila Krynytsia church hierarchy in the village. The policy of Austrian and
Russian governments in relation to local Old Believers is revealed. The paper mentions that Bila Krynytsia in
Bukovyna, founded in the 80-ies of XVIII century by Russian immigrants from Rumanian Lower Danube, was
transformed into a powerful center of Old Believers at Bila Krynytsia hierarchy abroad in the second half of
XIX century. Porkovskyi friary was opened in the village in 1803, and in 1852 – Uspenskyi nunnery. Bila Krynytsia
church hierarchy was established in this village on 27, October, 1846 through joining to Old Believer’s
Church of Metropolitan from Bosnia and Sarajevo Amvrosiy (Popovych). The first Episcopal chirotony took
place in Bila Krynytsia on 18, January, 1847. However, the untroubled activity of local metropolitans was infringed
at the end of November, 1847. Russia started demanding Austria to liquidate Old Believer’s hierarchy
and to close the friary. On 4, March, 1848 Austrian government closed the friary, however, soon it renewed its
operation after revolution of 1848. The consecration of Uspenskyi Cathedral, erected under project of Russian
architect A.V. Kuznetsov, took place in the nunnery on 15, July, 1908. The friary and nunnery in Bila Krynytsia
were liquidated when the Soviet power came. In 1944 Old Believers metropolitan’s cathedra was transferred
from Bila Krynytsia to Romanian city Brailu.